A innovative switchable polarity solvent, based on 1, 8‐diazabicyclo‐[5.4.0]‐ undec‐7‐ene and decanol was prepared for enrichment of aluminum in biological sample prior to analysis by flame atomic absorption spectrometry. (24th November 2017) - Arain, Mariam S.; Kazi, Tasneem G.; Afridi, Hassan I.; Khan, Naeemullah; Ali, Jamshed
Abstract : A novel switchable solvent (SS) extraction methodology has been used for the enrichment of aluminium (Al) in acid‐digested blood samples of patients with neurological disorders before proceeding to flame atomic absorption spectrometry. 1, 8‐Diazabicyclo[5.4.0]undec‐7‐ene and decanol in combination made a SS which reversibly changes from hydrophobic (nonpolar) to hydrophilic (polar) according to switch‐on and switch‐off phenomena in aqueous medium by exposure to anti‐solvent trigger (CO2 ). The SS polar micro‐emulsion was switched on by bubbling CO2, and switched off by heating from 40 to 70°C with exposure to N2 gas. The changes obtained in the structure and physical properties of the SS due to switching from lower polarity to higher polarity were investigated using Fourier transform infrared spectroscopic analysis. The SS was effectively analysed as an extractive medium for hydrophobic chelate of Al with 3, 5, 7, 2, 4‐pentahydroxyflavone (morin) and extracted in SS. Then hydrophobic enriched Al‐morin‐SS was treated with 1.0 M HNO3 and CO2 purging at various time intervals, switch to a miscible polar hydrophilic monophase state. The SS was easily recycled up to six times for further enrichment process. For the developed method, various parameters were optimized such as pH, volume of chelating reagent, CO2 purging time and pressure, and rate of heating. Under favourable conditions, enhancement factor and limit of detection were observed as 25 and 0.47 μg l −1, respectively, for 10 ml of samples/standards solution. The accuracy of the developed method was determined using certified reference material (SRM 3101a), with a standard addition procedure. The method was used for the pre‐concentration of Al in blood samples of patients with neurological disorders. Abstract : Innovative switchable polarity solvent, based on 1, 8‐diazabicyclo[5.4.0]undec‐7‐ene and decanol, for enrichment of aluminium in biological samples prior to analysis by flame atomic absorption spectrometry